Comparison Of HSRNAFold and RNAFold Algorithms for RNA Secondary Structure Prediction. - M. Mohsen, Abdulqader; Khader, Ahamad Tajudin; Ramachandram, Dhanesh (2009)
Ribonucleic Acid (RNA) has important structural and functional roles in the cell and plays roles in many stages of protein synthesis. The structure of RNA largely determines its function.